Efficacy of Dhataki ghrit Tulle in Comparison with Framycetine Sulphate Tulle in Management of Dusta Vrana - Satyam S. Supare; Kiran khandare (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Since life, humans have been susceptible to injury caused by wound healing deficiency.Modalities are needed to treat wounds from very early developmental stages. Ayurveda has various treatmentmodalities mentioned in texts for treatment of vrana. Modalities have been described in the form of localapplication, oral medication as per the stages and sadhyasadhyata of disease. Local use of ghrita with harbalformation is best practice for acharyas from ancient times until now. Aims and Objectives: Efficacy ofDhataki ghrit tulles in the management of Dusta vrana in comparison with Framycetine sulphate tulles. Andto study the effect of dhataki ghrit , plain ghrit and framycitene sulphate on dusta vrana. Methodology: inthis study total 210 patient will be divided randomly into 3 groups (70 each).In group A ( Experimental) Dhataki Grita tulle will be applied on wound locally in group B(Control) PlainGo ghrita will be applied and in group C(control) Framycetine sulplate tulle will be applied . Assessment willbe recorded as per criteria. Results: Changes will be observed in objective outcomes. Conclusion: Dhatakighrit tulle may be the best and cheap modality used as dressing material. Will be drown as per sutaible data.